Fatal and Near-Fatal Non-allergic Reactions in Patients with Underlying Cardiac Disease Receiving Benzathine Penicillin G in Israel and Switzerland - Berkovitch, Matitiahu; Ashkenazi-Hoffnung, Liat; Youngster, Ilan; Shaniv, Dotan; Dil-Nahlieli, Dorit; Gorelik, Einat; Schäublin, Martina; Stoller, Rudolf; Karra, Nour; Schwartzberg, Eyal (Frontiers in Pharmacology, 2017)
Benzathine Penicillin G (BPG) is commonly used for treatment of penicillin-susceptible infections and secondary prevention of rheumatic fever. Death following administration of BPG is extremely rare – only a handful of cases have been described in the literature since the 1950's. In this case series from Israel and Switzerland, we describe nine cases of serious adverse reactions - six fatal reactions and three near-fatalities - occurring within minutes of receiving intramuscular BPG. Allergic reactions or faulty administration were not implicated in any of the cases; however, all patients had cardiac risk factors. This case series describes a relatively rare risk that should be borne in mind when prescribing BPG.